2022
DOI: 10.3390/ijerph19031083
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recruitment Patterns of Sessile Marine Invertebrates According to Substrate Characteristics

Abstract: A community of benthic invertebrates, including sessile adult-stage invertebrates, can negatively effect corrosion, deformation, and increased fuel consumption by attaching to artificial structures, a phenomenon known as marine biofouling. Investigating the relationship between benthic communities and artificial structures or substrates (to which the organisms attach) can help clarify the factors influencing marine biofouling. Therefore, in our study, natural (stone) and artificial (rubber, tarpaulin, and iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…First, contrary to previous experiences in other areas [95,96], the artificial reefs of Genoa were not characterized by a lower species richness than the natural ones and did not represent an elective substrate for the settlement and propagation of alien species. Second, the persistent difference in community composition between natural and artificial reefs pointed out in many papers [97][98][99] was reduced where the artificial reefs were located in a mostly natural context: the proximity of the regional species pool appeared therefore more important than the age of the artificial reefs [77].…”
Section: Discussionmentioning
confidence: 99%
“…First, contrary to previous experiences in other areas [95,96], the artificial reefs of Genoa were not characterized by a lower species richness than the natural ones and did not represent an elective substrate for the settlement and propagation of alien species. Second, the persistent difference in community composition between natural and artificial reefs pointed out in many papers [97][98][99] was reduced where the artificial reefs were located in a mostly natural context: the proximity of the regional species pool appeared therefore more important than the age of the artificial reefs [77].…”
Section: Discussionmentioning
confidence: 99%
“…The dominant ascidians were the typical ones of port environments and during the summer months [51,56]. In the case of ascidians, it has been reported that their larvae prefer rough surfaces to settle [21,57] explaining why they are more abundant on the carbonated substrate. Moreover, during this species substitution process, there are species, such as Crisia denticulata, Savignyella lafontii, Botrylloides cf.…”
Section: Discussionmentioning
confidence: 99%
“…These trends were species-specific, C. gigas and M. galloprovincialis settled consistently irrespective of polymer type whereas C. savignyi preferred Nylon and S. caraniferus preferred PLA and Nylon. These differences likely reflect species-specific larval biological traits and ecology ( Ceccherelli & Rossi, 1984 ; Harris, 2008 ; Gosselin & Sewell, 2013 ; Cahill et al, 2016 ), and the physical and chemical properties of the substrates ( Siddik et al, 2019 ; Bae et al, 2022 ). Moreover, previous investigators reported that chemical cues released from the bacterial biofilm can affect the recruitment of macro-invertebrates larvae ( Wieczorek & Todd, 1998 ; Hadfield, 2011 ).…”
Section: Discussionmentioning
confidence: 99%